The Feiticeiro/a and the Categorical ‘Fetishist’: Sexuality Prescribed Through Psychiatric Classifications - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
In seeking to find a solid paradigm for the Feiticeiro/a character, it is tempting to approach the established psychiatric categories. Unfortunately, many of these suggest that people are ineffably different from others and that people will behave according to type in a predictable, even inevitable way. This chapter explores the World Health Organization’s International Classification of Diseases (ICD), which merely re-inscribes essentialist and determinist tendencies by means of processes akin to the phenomenon of cross-linguistic influence and linguistic fixity. The chapter explores further how this is embedded in the category of ‘fetishism’, ‘fetishistic transvestism’ and ‘transvestic fetishism’, which contain certain problematic vestigial tails of Freudian categories that make the psychiatric definitions of ‘fetishism’ unsuitable as a foundation for the Feiticeiro/a character.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé